FGF22 deletion causes hidden hearing loss by affecting the function of inner hair cell ribbon synapses - Hou, Shule; Zhang, Jifang; Wu, Yan; Junmin, Chen; Yuyu, Huang; He, Baihui; Yang, Yan; Hong, Yuren; Chen, Jiarui; Yang, Jun; Li, Shuna (Frontiers in Molecular Neuroscience, 2022)
Ribbon synapses are important structures in transmitting auditory signals from the inner hair cells (IHCs) to their corresponding spiral ganglion neurons (SGNs). Over the last few decades, deafness has been primarily attributed to the deterioration of cochlea hair cells rather than ribbon synapses. Hearing dysfunction that cannot be detected by hearing threshold is defined as hidden hearing loss (HHL). The relationship between ribbon synapses and FGF22 deletion remains unknown. Here, we used a six-week-old FGF22 knock-out mice model (FGF22-/-) and mainly focused on alteration in ribbon synapses by applying the auditory brainstem response test, the immunofluorescence staining, the patch-clamp recording and quantitative real-time PCR. In FGF22-/- mice, we found the decreased amplitude of ABR wave I, the reduced vesicles of ribbon synapses and the attenuated efficiency of Ca2+-triggered exocytosis which was suggested by the capacitance change for short stimuli. Quantitative real-time PCR revealed that FGF22-/- leaded to dysfunction of ribbon synapses by downregulating SNAP-25, Gipc3 and upregulating MEF2D expression, which were important for maintenance of ribbon synapses function. To conclude, our research showed that FGF22 deletion caused HHL by affecting the function of inner hair cell ribbon synapses, and may offer novel therapeutic targets to meet an ever-growing demand for deafness treatment.